As reformas educacionais de Benjamim Constant (1890-1891) e Francisco Campos (1930-1932): o projeto educacional das elites republicanas - Delaneze, Taís (Universidade Federal de São Carlos, 2008)
The study objects of this work are two educational reforms derived from the Public Federal Administration, namely the Reforms by Benjamim Constant (1890-1891) and Francisco Campos (1930-1932). Both are characterized by a series of decrees that legislated on several aspects of education and its degrees. The former was limited to regulating education in the Federal Capital (Rio de Janeiro), with the exception of high education, which was regulated nationwide. The later regulated the national education, thus representing a landmark in this sense. The Reform by Benjamim Constant was a product of the Proclamation of the Republic; and the one by Francisco Campos was the expanding of the conflagration of 1930. These two moments in the Brazilian political-economic context are the portrait of the same process: the bourgeois revolution in Brazil, which had not been finished in 1930, but, rather, had been provided with new impulses. The revolution that took place in Brazil did not follow the classical ways , which characterized, for example, the French Jacobinism. The process acclimated to Brazil was singular, but its analysis suggests similarities that are evidenced in the terms created by Lenin and Gramsci Prussian way and passive revolution, respectively. These two categories, which can be used as interpretative criteria for the Brazilian bourgeois revolution, develop the idea of conservative modernization, composed of modern and renewed elements that cause no revolutionary disruptions. While modernization is prompted by a segment of the conservative dominant class, revealing the reaction against the possibility of an effective transformation, it also absorbs part of the popular demand. In Brazil, the bourgeois spirit emerged from the agrarian aristocracy, which was responsible for the Modern State and contributed towards the capitalist development. In summary, the educational reforms resulting from this bourgeois context in Brazil, which were implemented by those conservative elites, reflected the educational thoughts by such elites. The primary education, essentially considered as the education for the people, was limited to Rio de Janeiro in the Reform by Benjamim Constant and not even mentioned in the Reform by Francisco Campos. Therefore, the education project of the republican elites included no expansion of the primary education, long retarding the establishment of both a public school, open to the subaltern classes, and a National Education System.
Keywords: Educação história; Reforma do ensino; Educação popular; Revolução burguesa no Brasil; CIENCIAS HUMANAS::EDUCACAO